Cardiovascular and Metabolic Disease: New Treatment and Future Directions - Caturano, Alfredo; Galiero, Raffaele (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The present Special Issue will lead you to discover the association between cardiovascular and metabolic diseases, through update reviews and original articles exploring the pathophysiological mechanisms underpinning this association and describing the latest results in term of cardiovascular event prevention. An interesting scientific journey that reflects the recent advances in pharmacological treatments and interventional procedures.